If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2h-35=12h-2h+3
We move all terms to the left:
2h-35-(12h-2h+3)=0
We add all the numbers together, and all the variables
2h-(10h+3)-35=0
We get rid of parentheses
2h-10h-3-35=0
We add all the numbers together, and all the variables
-8h-38=0
We move all terms containing h to the left, all other terms to the right
-8h=38
h=38/-8
h=-4+3/4
| 20m+0.5(m-4)=9 | | 48=-6r-10r | | x^2-10-24.75=0 | | 100f−50=50f+50 | | 5/c=2/12 | | 12=h-4 | | 1.2n+2.8=-2 | | 113=g-85 | | 95=-47+-4(t+6) | | -6(5a+2)+8a=-144 | | 5x+2x=7x-20 | | 4x-3=3x-11 | | 14x*2-5x-1=0 | | 3h+9=5-7 | | -9a+5=12 | | 7(x+5)-3(2x+3)-4.5=33.8 | | 14x²-5x-1=0 | | 33k^2-22k+11=0 | | 1/8-3/4x=1/2+1/8x | | 13x-7=3x-77 | | X*2+16x=0 | | 1/8-3/3x=1/2+1/8x | | 38=29-4(5-3w) | | 2x@=14 | | 5.1n+7=3+4.4(n-1) | | 4z+10=2z-6 | | 92=12+4p | | -1/5b-3/5=-2 | | 35=4x-33 | | 7(m-4)=-84 | | 152=-4x-7(-4x+16) | | 5=-1+x/4 |